Medical costs of lung cancer care in Japan during the first one or two years after initial diagnosis. (28th January 2021) - Awano, Nobuyasu; Izumo, Takehiro; Inomata, Minoru; Kuse, Naoyuki; Tone, Mari; Takada, Kohei; Muto, Yutaka; Fujimoto, Kazushi; Kimura, Hitomi; Miyamoto, Shingo; Igarashi, Ataru; Kunitoh, Hideo
Abstract: Objectives: Japan's healthcare expenditures, especially on oncology, are rapidly growing; however, there are scant data on actual costs and cost-effectiveness in the real world. The aim was to assess the medical costs and outcomes of patients with advanced lung cancer. Methods: We retrospectively investigated all patients who were diagnosed with advanced lung cancer at the Japanese Red Cross Medical Center between 1 January 2008 and 31 December 2018. Patients were classified into three cohorts according to the year of diagnosis—Cohort 1: 2008–2010, Cohort 2: 2011–2014 and Cohort 3: 2015–2018—and assessed for medical costs and outcome. Medical costs were divided into outpatient and inpatient costs and were calculated on a monthly basis. Results: Ninety-five patients with small cell lung cancer (SCLC) and 330 with nonsmall cell lung cancer (NSCLC) were included. There was a trend toward increased costs during the first two years after diagnosis in NSCLC patients, without changes in monthly costs, reflecting improved survival. Compared to Cohort 1, Cohort 3 patients with NSCLC had longer survival (median: 24 versus 12 months, P  < 0.001), with a median incremental cost of Japanese Yen 6 million during the initial two years. The proportion of outpatient costs increased over time, especially for NSCLC patients ( P  < 0.001). No changes in costs or survival were observed in SCLC patients. Conclusions: In NSCLC patients, medical costs increased with prolonged survival during the last decade. The costs on a monthly basis did not change. The proportion of outpatient costs increased. Abstract : There was no change in medical costs or survival rates for SCLC. In contrast, medical costs for the first two years after diagnosis increased and the prognosis improved for NSCLC.